AN OVERVIEW OF PERMIAN MARINE STRATIGRAPHY AND BIOSTRATIGRAPHY OF MONGOLIA - Manankov I.N.; Shi G.R.; Shen S.Z. (My University, 2006)
This paper summarizes the spatial distribution, stratigraphical divisions and biostratigraphical zonation schemes of Permian marine deposits in Mongolia. Where appropriate, correlations of the various Permian marine biostratigraphical units with those of adjacent regions are also reviewed and discussed. In general, Permian marine sequences are developed in two separate basins: one in central and northeastern Mongolia where the Permian stratigraphy and marine faunas bear strong similarities with those of the Transbaikal, Verkhoyansk and Kolyma-Omolon regions of southern and eastern Russia; and the other in southeastern Mongolia where the Permian marine faunas and rock sequences are closest to those of northeast China and southern Primorye of Far East Russia. © 2006 Elsevier Ltd. All rights reserved.
Keywords: BRACHIOPODS; MIXED FAUNAS; MONGOLIA; NORTHERN TRANSITIONAL ZONE; PERMIAN; Paleozoic::Permian; Палеозой::Пермская